Administrative management and productivity of the justice services of the judiciary in the province of Pataz, 2018-2020 (SCIÉNDO INGENIUM, 2021)
The present research determines the relationship that exists between administrative management and the productivity of the justice services of the Judicial Power in the province of Pataz, period: 2018 - 2020, for which it applies a methodology based on a quantitative - descriptive and correlational approach. and uses techniques such as documentary analysis and quantitative observation of the files of the Judicial Power of the province of Pataz. Likewise, the degree of association of the investigated variables is determined by means of Pearson's correlation coefficient. The results show that there is no significant relationship between the administrative management and the productivity of the justice services of the Judicial Power in the province of Pataz, period: 2018 - 2020, showing a low association between the variables. Regarding the index of congestion of the files, according to a Pearson correlation (r = 0,47) and for the resolution rate of the files (r = -0,063) at a significance level of 5%. Thus evidencing that the research hypothesis is not accepted.
Keywords: Administrative management; Productivity; Power of attorney